Investigation of potassium vapor time-resolved adsorption and potassium-sodium competitive adsorption by modified kaolinite. (15th December 2019) - Zhang, Xiuju; Liu, Huan; Xing, Haoxuan; Wang, Geyi; Li, Haiyan; Xiao, Kangxin; Liu, Wang; Yu, Yun; Yao, Hong
Highlights: An ingenious alkali vapor generator was designed to provide gas-solid reaction condition. Four classical adsorption models were applied to fit the time-resolved adsorption of K vapors. The Qe and initial adsorption rate of kaolinite increased by 100% after I-E modification. More K vapors were captured by kaolinite than Na due to the higher alkalinity. The maximum loading capacity occurred at the Na/K atomic ratio of approximately 1:1. Abstract: Frequent corrosion of heat transfer tubes in boilers, which was closely related to the massive corrosion sources, such as KCl and NaCl vapors in flue gas, restricted the safe and economic development of MSW incineration technology. This study attempted to alleviate corrosion by using the method of modified kaolinite adsorbing alkali vapors in furnace. Firstly, an ingenious alkali vapor adsorption platform with the advantage of simple operation and precise control was established. Based on this, the time-resolved adsorption of K vapors and the competitive adsorption of K/Na vapors by kaolinite and modified kaolinite were investigated. Four classical adsorption models were applied to mathematically describe the adsorption process. The pseudo-first order model was suitable for kaolinite and pseudo-second order model can be used to fit modified kaolinite. The corresponding rate-controlling steps were external mass transfer and chemisorption step. Accordingly, the equilibrium adsorption capacity of kaolinite and modified kaolinite was estimated as 17.41 and 32.30 mg/g, respectively. During the competitive adsorption of K/Na vapors, it was obvious that more K was captured by kaolinite than Na. It might be caused by the higher alkalinity of potassium, which had a higher tendency to react with acidic kaolinite. Maximum K-loading capacity of kaolinite occurred at the K/Na atomic ratio of approximately 1:1. After the structural calculation of alkali feldspar based on DFT, the most stable state of alkali feldspar occurred at the K/Na atomic ratio of 1:1, which might explain the maximum loading capacity at the K/Na ratio of 1:1.